Evaluating fresh and hardened properties of mortar composite with different types of modified polyethylene terephthalate (PET) materials as additives: modification effects, surface properties, shape factors - Wang, Zijian (2025)
Plastic disposal has become a challenge due to its challenging degradability, and plastics recycling is one of the ideal methods. Recycled plastic concrete has been widely researched as a possible way to store plastics permanently. An investigation on the modification and incorporation of polyethylene terephthalates (PET) on fresh and hardened properties of mortar composites (MCs) is performed in the study. The work provides understanding of the synergistic effects of plastic modification methods with different types of PET additives on MC properties and to explain behavior of modified PET in mortar composites. Modification methods include microwave radiation, chemicals oxidation and alkaline hydrolysis. These methods are applied on three types of structural PET materials (hard particles, hard strips and soft yarns). The properties of 0.5% to 3% PET added MCs include workability, compressive strength (CS), flexural strength (FS) and toughness are determined. At 28 days, 3% hydrolysis-treated PET yarns significantly increased FS by 69.6% and improved toughness by almost 15 times while CS with 3% PET particles modified by microwave radiation and chemicals oxidation are comparable to the control.